Physicochemical characteristics of lamb meat fed with cottonseed associated with calcium lignosulphonate - Leandro Pereira Lima; Cristiane Leal dos Santos Cruz; Thon Jovita Farias; Marcus Andrade Wanderley Júnior; Rodrigo Soares Junqueira; Ana Rosa Alves de Oliveira; Carla Fabrícia de Araújo Cordeiro; José Dantas Gusmão Filho (Acta Scientiarum. Animal Sciences, 2022)
The physicochemical characteristics of the meat from lambs fed diets containing whole or disintegrated cottonseed, associated or not with calcium lignosulfonate (LignoCaSO3), were evaluated. Thirty non-castrated Dorper x Santa Inês lambs, with an average of 24.9 ± 3.6 kg and four months of age were confined for 60 days in collective stalls and distributed in a completely randomized design with six replications. After slaughter, by means of contrasts, the averages of the parameters of the semimembranous and semitendinosus muscles were analyzed. The cottonseed increased cooking loss and ash, and reduced muscle weight, water holding capacity and red intensity. The disintegration of the cottonseed reduced the shear force in diets without LignoCaSO3, increased the protein and the loss by cooking and reduced the pH in the diets with the additive. The luminosity values increased with the disintegration of the cottonseed in diets with and without LignoCaSO3. The addition of LignoCaSO3 increased the weight of the muscle, protein, ash, pH, shear strength and the intensity of red. Moisture, lipids and yellow intensity were not influenced by the diets. Even changing the physical-chemical characteristics, the cottonseed with or without LignoCaSO3 does not change the quality of the meat